Penyelenggaraan Pendidikan Inklusif Anak Berkebutuhan Khusus (Studi Multi Situs di SDN-4 Palangka dan SDN-3 Langkai Kota Palangka Raya) - Bedha Tamela; Joni Bungai; Wawan Kartiwa (Journal of Environment and Management, 2020)
Every Indonesian citizen has the right to get education according to Article 31 paragraph (1) of the 1945 Constitution. To date, education for children with special needs (Anak Berkebutuhan Khusus/ABK) is held separately from the majority one. The separation, further, leads to the idea of inclusive education for all. This research aims to describe the implementation of inclusive education in SDN 4 Palangka and SDN-3 Langkai in Palangkaraya City. Besides, it looks for the supporting and inhibiting factors in its implementation. The data derived from observation, interviews and document analysis. The results confirm that the current implementation of inclusive education still needs substantial improvement and support, primarily in terms of qualified teaching staffs, facilities/infrastructure and funding. We found eleven supporting factors and four inhibiting factors influencing the implementation of inclusive education in SDN 4 Palangka and SDN-3 Langkai in Palangka Raya City.